ENDOWMENT POLICY - Machakos university (My University, 2018)
Machakos University endeavours to achieve sustainably, industrial and socioeconomic transformation of our communities. This aspiration requires prudent resource mobilization and management which is the intent of this Endowment Policy. The Policy seeks to support Machakos University, especially on themes that are strategically beneficial to the institution, the neighboring communities and to the entire country. It provides a framework for steady flow of funds to Machakos University, thus focusing on stability and certainty in support of students, teaching,institutional research and innovation projects. Broadly, this policy is intended to facilitate consistent investment approach that cultivates perpetual long-term returns. This permits access to high-quality investment vehicles and provides a broader set of investment possibilities while fostering intergenerational equity. The principle of intergenerational equity will ensure that future generations of students and schools receive at least the same level of support from Machakos University’s endowment fund just as the current generation enjoys. It is therefore in my trust that this policy lays infrastructural support necessary for endowment fund best practices. Prof. Lucy Irungu, PhD Vice- Chancellor & Professor of Entomology